Treatments for chronic myeloid leukemia: a qualitative systematic review - Ferdin; R; Mitchell SA; Batson S; Tumur I (Journal of Blood Medicine, 2012)
Roxanne Ferdinand,1 Stephen A Mitchell,2 Sarah Batson,2 Indra Tumur11Pfizer, Tadworth, UK; 2Abacus International, Bicester, UKBackground: Chronic myeloid leukemia (CML) is a myeloproliferative disorder of blood stem cells. The tyrosine kinase inhibitor (TKI) imatinib was the first targeted therapy licensed for patients with chronic-phase CML, and its introduction was associated with substantial improvements in response and survival compared with previous therapies. Clinical trial data are now available for the second-generation TKIs (nilotinib, dasatinib, and bosutinib) in the first-, second-, and third-line settings. A qualitative systematic review was conducted to qualitatively compare the clinical effectiveness, safety, and effect on quality of life of TKIs for the management of chronic-, accelerated-, or blast-phase CML patients.Methods: Included studies were identified through a search of electronic databases in September 2011, relevant conference proceedings and the grey literature.Results: In the first-line setting, the long-term efficacy (up to 8 years) of imatinib has been confirmed in a single randomized controlled trial (International Randomized Study of Interferon [IRIS]). All second-generation TKIs reported lower rates of transformation, and comparable or superior complete cytogenetic response (CCyR), major molecular response (MMR), and complete molecular response rates compared with imatinib by 2-year follow-up. Each of the second-generation TKIs was associated with a distinct adverse-event profile. Bosutinib was the only second-generation TKI to report quality-of-life data (no significant difference compared with imatinib treatment). Data in the second- and third-line setting confirmed the efficacy of the second-generation TKIs in either imatinib-resistant or -intolerant patients, as measured by CCyR and MMR rates.Conclusion: Data from first-line randomized controlled trials reporting up to 2-year follow-up indicate superior response rates of the second-generation TKIs compared with imatinib. Current evidence from single-arm studies in the second-line setting confirm that nilotinib, dasatinib, and bosutinib are valuable treatment options for the significant subgroup of patients who are intolerant or resistant to imatinib treatment.Keywords: chronic myeloid leukemia, imatinib, nilotinib, dasatinib, bosutinib